Implikasi Pengaruh Ulama Terhadap Hala Tuju Perubahan Pemikiran Politik Masyarakat Islam Wilayah Utara Semenanjung Malaysia dari 1950an Hingga 1990an - Ahmad, Shukri (Jurnal Usuluddin, 2001)
Islam and Malays are closely related. Some scholars in Malaysia more often name Malays as Muslims and vice versa. This is an indication of predominance of Islam in the Malay thought. The centre of the development Muslim thought is the ’Ulama and it could be said that the essence of Malay thought is the ’Ulama themselves. Efforts towards achieving the independence of Malaysia was initiated by them. For instance, the first Malay political party, Hizb al-Muslim was established by this group. After independence, the political parties, UMNO and PAS, become the back bone of Malay political activities involving also this group. This article examines the effect of their influence in the Malays political thought. Some related contemporary political issues will be highlighted.